2017
DOI: 10.5125/jkaoms.2017.43.6.363
|View full text |Cite
|
Sign up to set email alerts
|

Association between headache and temporomandibular disorder

Abstract: Headaches are one of the most common conditions associated with temporomandibular disorder (TMD). In the present paper, we evaluated the relationship between headache and TMD, determined whether headache influences the symptoms of TMD, and reported two cases of TMD accompanied by headache. Our practical experience and a review of the literature suggested that headache increases the frequency and intensity of pain parameters, thus complicating dysfunctional diseases in both diagnostic and treatment phases. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…SB may be associated with TMDs, and headache is often an accompanying symptom (33). Wagner et al have showed an association between headache and TMDs ( p < 0.001) and between headache and anxiety ( p = 0.002), but not between headache and bruxism ( p = 0.670) (17).…”
Section: Discussionmentioning
confidence: 99%
“…SB may be associated with TMDs, and headache is often an accompanying symptom (33). Wagner et al have showed an association between headache and TMDs ( p < 0.001) and between headache and anxiety ( p = 0.002), but not between headache and bruxism ( p = 0.670) (17).…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular joint disorder has been reported by service members and veterans with exposure to IEDs and blast injury (98) and posttraumatic stress disorder (PTSD) (99). Of relevance to the data presented, headaches are the most commonly reported condition associated with temporomandibular joint disorders (100). Veterans with blast mTBI report high prevalence of chronic daily headaches and migraines, as compared to the general population with TBI and concussion (101)(102)(103).…”
Section: Headache and Chronic Painmentioning
confidence: 90%
“…Abouelhuda et al 20 in their practical experience and a review of the literature suggested that headache increases the frequency and intensity of pain parameters, complicating TMD in both diagnostic and treatment phases. Therefore, early and multidisciplinary treatment of TMDs is necessary to avoid overlap of painful events that could become chronic.…”
Section: Discussionmentioning
confidence: 99%